Pemanfaatan PRIMS dalam Pengelolaan Informasi yang Efisien Pada Departemen Sistem Manajemen Terpadu dan Inovasi Pada PT X - Merry Agustina; Ahmad Yani Ranius (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2025)
The utilization of integrated information systems is essential to support efficient organizational information management. PT X Palembang has implemented PRIMS (Platform Repository Integrated Management System) as a web-based document management system used by all employees, with the Integrated Management System & Innovation Department acting as the administrator. This study aims to analyze the utilization of PRIMS as an efficient information management tool and to identify its benefits, challenges, and constraints. This research employs a descriptive method with data collection techniques including observation, interviews, and literature review. The results indicate that PRIMS improves document management efficiency through features such as document search, document input and revision, user access control, and security features including watermarking and metadata history. However, the implementation still faces several constraints, including technical issues during data migration, limitations in network infrastructure, and limited administrative resources. Overall, PRIMS provides a positive contribution to improving information management efficiency at PT X Palembang.